Cummins C-105 diesel engine - Office of Public Relations, California State Polytechnic College, San Luis Obispo::::::::: (1963)
Charles Grace, Cummins Engine Company, presents Cummins C-105 diesel engine to Cal Poly Agricultural Engineering Department. Left to right: Dr. Dale Andrews (Ag Eng. Dean); Warren T. Smith (dean of Agriculture); J.R. Neal (general manager Cummins Sales and Service).